Torpedo maculopathy: disease spectrum and associated choroidal neovascularisation in a paediatric population - Shirley, Katherine; O’Neill, Marie; Gamble, Rachel; Ramsey, Anne; McLoone, Eibhlin (Eye (London), 2018)
Purpose Torpedo maculopathy is a rare lesion of the retinal pigment epithelium. This study set out to look at these lesions in the paediatric population and determine the spectrum and features of the disease. Methods The paediatric ophthalmology database was used to identify eight children with torpedo maculopathy between 2012 and 2017. Fundal images and optical coherence tomography (OCT) was used to analyse the cases. Results Eight patients with torpedo maculopathy were identified, making the prevalence approximately 2 per 100,000 population under 16 years old. The OCT images were classified using the previously described subtypes: Type 1 in patients 5 and 6 and Type 2 in patients 1, 2, 3, 4 and 8. The average age of presentation of Type 1 and Type 2 lesions was 8 and 7 years old respectively. We also report patient 8, who is the youngest reported case of choroidal neovascular membrane associated with torpedo maculopathy. Good anatomical response to a single injection of anti-Vegf was shown. Conclusions This study is the first case series of torpedo maculopathy in the paediatric population. Contrary to previous reports of two distinct types of lesion on OCT representing different stages of the same disease, our case series indicates that Type 1 and Type 2 lesions are in fact different phenotypic entities both of which can occur at a young age. We also present the associated risk of choroidal neovascular membrane formation which is an important consideration for long term follow-up.